Music in therapeutic practice : using rhythm to bridge communication barriers - Ready, Trisha (Rowman & Littlefield, 2016)
Music in Therapeutic Practice: Using Rhythm to Bridge Communication Barriers builds upon an emerging awareness in psychotherapy that music can create therapeutic rapport with patients. Music has been described as our first language, beginning with our mother's heartbeat. Ready illustrates how music provides alternative access to patients undergoing severe mental health issues by interweaving the psychoanalytic theories of Wilfred Bion, Daniel Stern, and others with those of ethnomusicologists, psychobiologists, and neurobiologists who believe our early urges toward music are attempts to social.